Integrated Care for the Elderly in the Primary Health Care setting Oman: The Scope and Experience - Al Rashidi, Badria; Al Wahaibi, Ahmed H.; Al Awaidy, Salah (International Journal of Innovative Research in Medical Science, 2022)
Many underlying physiological changes occur with age, and in elderly people, there is an increased risk of chronic disease and care dependence. Globally, the number of elderly people increases considerably in a relatively short period of time and the need for further support is also increasing exponentially. As the number of elderly people continues to grow along with their longevity, the need for long-term health care will increase significantly. Ultimately, the health care system faces a number of challenges, including long-term care, which includes activities related to the risk of age-related disabilities associated with chronic diseases. We examine the status of the elderly program in Oman, the achievements, and gaps in achieving the Ministry of Health's vision in 2050. The review eluded that the elderly program is headed in the right direction, however, the program still has unmet needs of physical fitness-related care, psychological health care, community support, and the leaving the environment. The findings of this review also underlined the importance of care models and support services specifically based on the needs of the elderly.